JAMINAN PERUNDANG-UNDANGAN TENTANG EKSISTENSI LEMBAGA KEUANGAN SYARI`AH DI INDONESIA - Amin Suma, Muhammad (Islamic University of Indonesia, 2003)
The author of this article explains that Islamic economics system actually has developed in Indonesia. But because of Dutch Colonized era and the government after, Islamic economics system has been marginalized in Indonesia. In the beginning of 1990s, Islamic economics particularly in monetary system that indicates the operating of Bank Muamalat Indonesia (BMI-Muamalat Bank of Indonesia) in 1992, Lembaga Keuangan Syariâah (LKBS-Syariah Finance Institution), and Lembaga Keuangan Syariâah Non Bank (LKSBB-Non-Bank Syariah Finance Institution).These institutions emerge at the time when economic crisis happen in Indonesia. According to the writer of the article the growth of Islamic economics institutions in Indonesia gives hopes. But the problem in the context of those is the legislations that regulate the institution do not appear yet.